Subscription Based Architecture For Secured Group Key Management By Using Linear Equation - kumar Mangal, Sorabh; k. Navin, Mr.; M. Sayeekumar, Dr. (International Journal of Engineering and Technology, 2018)
Various applications which are running on to a network require communicating of data onto one or many members. Security is the main focused area in group communication, thereby security of data in the groups is one of the main task for controlling and maintaining access. Unfortunately, IP multicast is not providing any security over the group communication. Therefore it is mandatory to have the group communication with common group key. Group key Management is a fundamental mechanism for secured multicast communication. In group communication it is mandatory for security reasons when the user is joining or evicting the group, the group key has to be change so that the user will unable to receive or fetch information or data, that means user will be unable to receive any new information after leaving the group likewise the new user will not be able to fetch the old information or data. The efficiency of the group key communication depends on the computational cost and communicational cost. The cost should be minimum for both join and eviction of users from the group. The proposed model with subscription algorithm in which divide the group in to subgroups like hybrid model on the basis of years, months, days and hours further divide these subgroups in small subscription time intervals. Linear equation is to be used to calculate these intervals by which predicted request is to be calculated. When the new user will join the group according to their subscription time will get the group and rekeying process will occur. After the subscription period get over the whole time interval of sub-group will be discarded so no rekeying is needed that means eviction cost is reduced to almost Zero (0).Â Â